Characteristics, Comorbidities, and Outcomes in a Multicenter Registry of Patients With Human Immunodeficiency Virus and Coronavirus Disease 2019. (9th September 2020) - Dandachi, Dima; Geiger, Grant; Montgomery, Mary W; Karmen-Tuohy, Savannah; Golzy, Mojgan; Antar, Annukka A R; Llibre, Josep M; Camazine, Maraya; Díaz-De Santiago, Alberto; Carlucci, Philip M; Zacharioudakis, Ioannis M; Rahimian, Joseph; et al.
Abstract: Background: People living with human immunodeficiency virus (HIV) may have numerous risk factors for acquiring coronavirus disease 2019 (COVID-19) and developing severe outcomes, but current data are conflicting. Methods: Health-care providers enrolled consecutively, by nonrandom sampling, people living with HIV (PWH) with lab-confirmed COVID-19, diagnosed at their facilities between 1 April and 1 July 2020. Deidentified data were entered into an electronic Research Electronic Data Capture (REDCap) system. The primary endpoint was a severe outcome, defined as a composite endpoint of intensive care unit (ICU) admission, mechanical ventilation, or death. The secondary outcome was the need for hospitalization. Results: There were 286 patients included; the mean age was 51.4 years (standard deviation, 14.4), 25.9% were female, and 75.4% were African American or Hispanic. Most patients (94.3%) were on antiretroviral therapy, 88.7% had HIV virologic suppression, and 80.8% had comorbidities. Within 30 days of testing positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), 164 (57.3%) patients were hospitalized, and 47 (16.5%) required ICU admission. Mortality rates were 9.4% (27/286) overall, 16.5% (27/164) among those hospitalized, and 51.5% (24/47) among those admitted to an ICU. The primary composite endpoint occurred in 17.5% (50/286) of all patients and 30.5% (50/164) of hospitalized patients. Older age, chronic lung disease, and hypertension were associated with severe outcomes. A lower CD4 count (<200 cells/mm 3 ) was associated with the primary and secondary endpoints. There were no associations between the ART regimen or lack of viral suppression and the predefined outcomes. Conclusions: Severe clinical outcomes occurred commonly in PWH with COVID-19. The risks for poor outcomes were higher in those with comorbidities and lower CD4 cell counts, despite HIV viral suppression. Clinical Trials Registration: NCT04333953. Abstract : Severe clinical outcomes occurred commonly in people living with human immunodeficiency virus (HIV) who contracted coronavirus disease 2019 (COVID-19): severe outcomes were associated with age, chronic lung disease, hypertension, and lower CD4 counts, but not HIV viremia or antiretroviral regimen.